2021
DOI: 10.1093/aob/mcab013
|View full text |Cite
|
Sign up to set email alerts
|

Foliar nutrient allocation patterns in Banksia attenuata and Banksia sessilis differing in growth rate and adaptation to low-phosphorus habitats

Abstract: Background and aims Phosphorus (P) and nitrogen (N) are essential nutrients that frequently limit primary productivity in terrestrial ecosystems. Efficient use of these nutrients is important for plants growing in nutrient-poor environments. Plants generally reduce foliar P concentration in response to low soil P availability. We aimed to assess ecophysiological mechanisms and adaptive strategies for efficient use of P in Banksia attenuata (Proteaceae), naturally occurring on deep sand, and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
5
1
Order By: Relevance
“…Compared with the leaf P content in the two species, the leaf N content of T. ramosissima was higher than K. caspica . These findings differs from results on Hakea prostrata (Proteaceae) which showed that P availability does not affect leaf N content ( Prodhan et al, 2019 ), but correlated leaf N and leaf P content was similar, and enhanced as increasing soil available-P concentration or groundwater available-P concentration ( Han et al, 2021 ). The leaf N content of both species was lower than both those in global soils ( Cleveland and Liptzin, 2007 ; Xu et al, 2013 ), and lower than results previously reported on A. sparsifolia in this area ( Zhang et al, 2018 ; Gao et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Compared with the leaf P content in the two species, the leaf N content of T. ramosissima was higher than K. caspica . These findings differs from results on Hakea prostrata (Proteaceae) which showed that P availability does not affect leaf N content ( Prodhan et al, 2019 ), but correlated leaf N and leaf P content was similar, and enhanced as increasing soil available-P concentration or groundwater available-P concentration ( Han et al, 2021 ). The leaf N content of both species was lower than both those in global soils ( Cleveland and Liptzin, 2007 ; Xu et al, 2013 ), and lower than results previously reported on A. sparsifolia in this area ( Zhang et al, 2018 ; Gao et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with results from this study where T. ramosissima growth was more likely limited by P while K. caspica growth was not. In addition, the higher leaf N content and leaf N:P ratios suggest that more leaf P was allocated to nucleic acid-P ( Figure 4 ; Han et al, 2021 ). Interestingly, however, the ratios of leaf N:P Fraction in each P fraction, with the exception of residual-P, were higher in T. ramosissima than in K. caspica ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, LP conditions significantly enhanced the R/S ratio in this study ( Supplementary Table S2 ). Previous research found that the increased allocation of photosynthates to roots, which leads to an increased root-to-shoot ratio and P acquisition, was linked to how crop plants responded to P deprivation ( Han et al., 2021 ). In plants with a P shortage, it was found that allocating biomass to root development improves P uptake ( Brown and Linch, 2001 ; Wen et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%